Role of blood mSEPT9 in evaluating tumor burden and disease monitoring in colorectal cancer patients. Issue 11 (30th September 2021) - Jiang, Huiqin; Yu, Qian; Chen, Xinning; Zhang, Chunyan; Shen, Junfei; Shen, Minna; Yang, Yihui; Wang, Beili; Pan, Baishen; Guo, Wei
Abstract: Purpose: This study aimed to investigate the correlation between mSEPT9 and tumor burden as well as the role of mSEPT9 in monitoring colorectal cancer (CRC) patients. Methods: A total of 309 patients were recruited and received mSEPT9 detection in this retrospective study. Clinicopathologic characteristics were collected, including age, gender, differentiation, gene mutation, stage, and tumor markers. The correlation between mSEPT9 and clinical tumor burden was analyzed. A relative mSEPT9 value was determined using the ΔΔ C t method. Results: The overall positivity rate of mSEPT9 was 39.8% in CRC patients. mSEPT9 status was significantly associated with disease status and tumor markers (CEA and CA19‐9). The mSEPT9 positivity rates were 15.6%, 50.0%, 64.4%, and 70.0% for P0M0, P1M0, P0M1, and P1M1 patients, respectively ( p < 0.001). Among 137 CRC patients who received mSEPT9 assay before surgery, the pre‐operation mSEPT9 positivity rate increased significantly from stage I to stage IV (Stage I vs. II vs. III vs. IV 25% vs. 59.1% vs. 57.1% vs. 70.0%, respectively). Consecutive blood samples were obtained from 26 patients during therapy. The patients with increased mSEPT9 levels showed a higher progression rate. Conclusions: mSEPT9 was a biomarker reflecting tumor burden, and serial detections of mSEPT9 could be a promising strategy for disease monitoring in CRC patients. Abstract : Few studies have been conducted to investigate the association between mSEPT9 status and tumor burden, and the role of mSEPT9 level in predicting response is still unclear. The present study showed that ctDNA mSEPT9 was positively correlated with tumor status, and pre‐operation mSEPT9 was an independent predictor of the UICC stage. Serial detecting of mSEPT9 could be a promising strategy for disease monitoring in CRC patients.